Penerapan Budaya 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) terhadap Produktivitas Karyawan - Rohma Bekti, Ida; Cahyadi, Nur (Value : Jurnal Manajemen dan Akuntansi, 2024)
5S is a work system with an effectiveness perspective based on a specific industry culture. The 5S is a work system with an effectiveness perspective based on a specific industrial culture. The aim of this research is to test the application of 5S Culture (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) to the productivity of PT PLN NP UMRO employees. The research sample used was 39 people taken from employees of PT PLN NP UMRO Gresik Region as respondents to the research by distributing questionnaires. Testing using Systematic Random Sampling using a quantitative approach by processing questionnaire data obtained using the SmartPLS 4 application. The results of this study show that: (1) Seiri has a positive and significant influence on Employee Productivity (2) Seiton has a positive and significant influence on Employee Productivity (3) Seiso has a negative and insignificant influence on Employee Productivity (4) Seiketsu has a negative and insignificant influence on Employee Productivity (5) Shitsuke has a negative and insignificant influence on Employee Productivity. Keywords: Seiri, Seiton, Seiso, Seiketsu, Shitsuke, Work productivity